The T-cell-receptor repertoire in the synovial fluid of a patient with rheumatoid arthritis is polyclonal. - Yasushi Uematsu; Henning Wege; A. H. Straus; Michael Ott; Wilhelm Bannwarth; Jerry S. Lanchbury; G S Panayi; Michael Steinmetz (1991)
We have analyzed the T-cell-receptor repertoire expressed in the synovial fluid of a patient with rheumatoid arthritis by using an inverse polymerase chain reaction. Total RNA was isolated from Ficoll-purified mononuclear cells and converted into circularized double-stranded cDNA. Specific amplification of alpha- and beta-chain variable regions (V alpha and V beta) was achieved with inverted alpha- and beta-chain constant region (C alpha and C beta) primer pairs, and the amplification products were cloned into phage vectors. A total of 78 alpha and 76 beta clones were sequenced, and 67 and 72 productively rearranged alpha and beta genes were identified, respectively. Thirty-one V alpha, 33 alpha-chain joining region (J alpha), 29 V beta, and 12 beta-chain joining region (J beta) gene segments were found in the productively rearranged clones, indicating that the T-cell repertoire expressed in the synovial fluid of this RA patient is highly heterogenous and polyclonal. Comparison of peripheral blood and synovial fluid repertoires showed that the most abundant V beta sequences, V beta 2.1 and V beta 3.1, were enriched in the inflamed joint by a factor of 2 to 3. It is possible that T cells expressing these V beta gene segments, which recognize bacterial superantigens, play a role in the disease.